2018
DOI: 10.1177/1471301217752707
|View full text |Cite
|
Sign up to set email alerts
|

Does personal experience of dementia change attitudes? The Bristol and South Gloucestershire survey of dementia attitudes

Abstract: We recommend you cite the published version. The publisher's URL is: https://doi.org/10.1177/1471301217752707Refereed: Yes (no note) Disclaimer UWE has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material. UWE makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited.UWE makes no representation that the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 24 publications
2
23
1
Order By: Relevance
“…6 Additionally, experiencing dementia promoted participants' understanding, thereby reducing the stigma of dementia. 29 We found similar results for the participants' total sense of community scores. The improvement in the sense of community is consistent with a previous study, in which dementia education enhanced the general population's empathy for people with dementia, leading to the community's involvement in supporting people with dementia.…”
Section: Discussionsupporting
confidence: 73%
“…6 Additionally, experiencing dementia promoted participants' understanding, thereby reducing the stigma of dementia. 29 We found similar results for the participants' total sense of community scores. The improvement in the sense of community is consistent with a previous study, in which dementia education enhanced the general population's empathy for people with dementia, leading to the community's involvement in supporting people with dementia.…”
Section: Discussionsupporting
confidence: 73%
“…The survey was available to complete electronically through a survey link of SurveyMonkey [43] that was sent to staff email addresses via a gatekeeper. Hard copy surveys were also available in all patient care areas to complete and return to a central location via internal mail for those without access to or unable to use a computer [40,44]. All grades of staff including support staff (e.g.…”
Section: Design Setting and Participantsmentioning
confidence: 99%
“…disease prevalence, symptoms, risk factors, prevention, assessment or treatment) to more specifically guide educational initiatives to help sensitize individuals to what they do not know about dementia [38]. Thirdly, the study might have benefitted from having more specific information or factors explaining the level of dementia awareness and knowledge in hospital staff, including overall educational level [36,41], whether they worked or were in contact with people living with dementia on a daily basis [40] or their confidence level working with people living with dementia [31].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…(37)), but contrary to what one might expect, it was not a strong indicator for a more positive attitude. A recent study using the validated measure Approaches to Dementia Questionnaire (ADQ) to assess participants' attitudes towards dementia demonstrated that increased contact with people with dementia was associated with increased ADQ scores re ecting more hope and person-centred attitudes towards dementia (40).…”
Section: Introductionmentioning
confidence: 99%